REVIEWING RADICAL SUBJECTS IN THE SHORT STORY VAMPIRE BY INTAN PARAMADITHA SUBJECT PERSPECTIVE SLAVOJ ZIZEK - Musyaffa, Mochamad (University of Brawijaya, 2023)
The short story Vampire by Intan Paramaditha tells about a woman who works as a secretary. In matters of thought, he must comply with norms or symbolic orders to become a professional secretary. This study discusses the subject formation in the short story Vampire. The method used in this research is critical discourse analysis. The stages carried out in this research are; First, define material objects and formal objects. The object material used is the vampire short story by Intan Paramaditha. While the formal object is the study of the subject of Slavoj Å½iÅ¾ek. Second, find and record data related to the object of research. Third, do the analysis with the method of critical discourse analysis. The analysis will be devoted to linguistic aspects and contexts related to the subject of Slavoj Å½iÅ¾ek's theory. The results of this study indicate that the subject failed to become an authentic subject. She was only able to get out of the symbolic order that she maintained, namely the norms of being a professional secretary. In the end he crossed the line and gave up his symbolic order. Even though the action is done consciously, the action taken by the subject has a specific purpose and motive, namely to fulfill his desires.Keywords: subject, radical, Å½iÅ¾ek, blood, Vampire